PENGARUH KERAGAMAN PRODUK, CITA RASA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN - Melda Melda; Eti Arini; Ade Tiara Yulinda (UM. Bengkulu, 2020)
The economic industry is currently the largest industry throughtout the world and contribute large development on world economy. Specifically, in Bengkulu Province, the strategies that should be applied to attract and increase the economy such as a variety of product diversity, taste and brand image. This study aims to analyze the effect of product diversity, taste and brand Image at the Lia Jaya Crackers factory at Talang Pauh Village, Pondok Kelapa Bengkulu, Central Bengkulu. The samples were 125 respondents by using accident sampling technique. The data that has been collected by using Multiple Linear Regression analysis techniques, determination coefficient analysis (R2), and partial test (t test), simultaneous test (f-test). The results of the study can be seen from the diversity of products were positive and significant effect on purchasing decisions. Product Diversity (X1), Taste (X2), Brand Image (X3) jointly influence the Purchasing Decision (Y) at Lia Jaya Crackers, Talang Pauh Village, Pondok Kelapa District, Central Bengkulu. This is evidenced by the F-test showed the value of F_count > F-table 1.190 (102.504> 1.190) and (sig-Î± = 0.000 <0.05). This means H0 is rejected and Ha is accepted. The correlation coefficient test obtained value R-value = 0.847 and determination coefficient R ^ 2 =0.718, value has the meaning that Product Diversity (X_1), Taste (X2), Brand Image (X3) contribute significantly to effect of 0.718 or 71.8% on the purchasing decision (Y) at the Lia Jaya Crackers Purchase Decision, while the remaining 28.2% is not influenced by other variables not discussed in this study. Keywords: Product Diversity, Tastes, Brand Image, Purchasing Decisions